HS‐CRP Modifies the Prognostic Value of Platelet Count for Clinical Outcomes After Ischemic Stroke - Liu, Fanghua; Yang, Pinni; Wang, Yinan; Shi, Mengyao; Wang, Ruirui; Xu, Qingyun; Peng, Yanbo; Chen, Jing; Zhang, Jintao; Wang, Aili; Xu, Tan; Zhang, Yonghong; et al. (Journal of the American Heart Association, 2023)
Background We examined whether the relationship between baseline platelet count and clinical outcomes is modulated by HS-CRP (high-sensitivity C-reactive protein) in patients with ischemic stroke. Methods and Results A total of 3267 patients with ischemic stroke were included in the analysis. The primary outcome was a combination of death and major disability at 1 year after ischemic stroke. Secondary outcomes included major disability, death, vascular events, composite outcome of vascular events or death, and an ordered 7-level categorical score of the modified Rankin Scale at 1 year. Multivariate logistic regression and Cox proportional hazards regression models were used to assess the association between the baseline platelet count and clinical outcomes stratified by HS-CRP levels when appropriate. There was an interaction effect of platelet count and HS-CRP on the adverse clinical outcomes after ischemic stroke (all <0.05). The elevated platelet count was significantly associated with the primary outcome (odds ratio [OR], 3.14 [95% CI, 1.77-5.58]), major disability (OR, 2.07 [95% CI, 1.15-3.71]), death (hazard ratio [HR], 2.75 [95% CI, 1.31-5.79]), and composite outcome of vascular events or death (HR, 2.57 [95% CI, 1.38-4.87]) among patients with high HS-CRP levels (all <0.05). Conclusions The HS-CRP levels had a modifying effect on the association between platelet count and clinical outcomes in patients with ischemic stroke. Elevated platelet count was significantly associated with adverse clinical outcomes in patients with ischemic stroke with high HS-CRP levels, but not in those with low HS-CRP levels. These findings suggest that strategies for anti-inflammatory and antiplatelet therapy should be developed according to the results of both platelet and HS-CRP testing.